Study on the mud swimming motion of Paramisgurnus dabryanus. (August 2022) - Wu, Liyan; Li, Wanpeng; Ni, Yonggang; Liu, Wenbing; Liu, Zeyu; Liu, Cuihong; Fan, Xiaoguang
In the context of the rapid development of bionic technology, inspired by the swimming behavior of fish, a variety of robotic fish have been designed and applied to different underwater works and even military applications. However, in some operations, such as detection and salvage, vehicles need to travel under mud, a medium that is different from fluids. This complicating factor put higher requirements on robotic fish design. In this study, Paramisgurnus dabryanus, a fish species adept at swimming into the mud, was taken as a research object to investigate its profile and mud swimming behavior. First, a three-dimensional (3D) image scanner is used for profile scanning to acquire the point cloud data of the profile features of the loach. After modification, data coordinate points are extracted and used to fit the profile curve of loach and build geometric and mathematical models by means of Fourier function fitting. The next step includes the analysis of the motion of loach, determination of main parameters of the wave equation, and establishment of the fish body wave curve of a loach in the swimming using MATLAB software. Saturated mud having a water content of 37% is adopted as an environmental medium to numerically simulate the swimming behavior in mud, identifying the distribution of vortex path, and velocity field of loach's motion. The rationality of simulation results is verified by the loach mud swimming test, and the simulating results agree well with the experimental data. This study lays a preliminary foundation for the outer contour design of the robotic fish operating under mud and aims to carry out the drag reduction and accelerating design of the robotic fish. The robotic loach may be applied in fishery breeding, shipwreck salvage operations, and so on.